2013
DOI: 10.1002/lt.23593
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation after stage II palliation for hypoplastic left heart syndrome

Abstract: The association of biliary atresia (BA) with congenital heart diseases has been extensively described, and there are a number of reports on the outcomes of patients in this group who undergo liver transplantation (LT). The intraoperative management and the timing of LT for patients with end-stage liver disease are matters of debate, especially when complex heart diseases are involved. This report describes the outcome after LT for a pediatric recipient with BA and hypoplastic left heart syndrome. The patient u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Bacha et al 10 concluded that patients with end-stage liver disease presented with higher morbidity and mortality in open-heart surgery with cardiopulmonary bypass than children with no liver disease, but the intervention represents a reasonable option for a chance at LT and/or long-term survival. Six publications describe LT in patients with a wide range of complex congenital heart defects 1,9,[11][12][13][14]. The heart procedures were performed before LT in five patients, during LT in one patient (patent ductus arteriosus), and after LT on two occasions.…”
mentioning
confidence: 99%
“…Bacha et al 10 concluded that patients with end-stage liver disease presented with higher morbidity and mortality in open-heart surgery with cardiopulmonary bypass than children with no liver disease, but the intervention represents a reasonable option for a chance at LT and/or long-term survival. Six publications describe LT in patients with a wide range of complex congenital heart defects 1,9,[11][12][13][14]. The heart procedures were performed before LT in five patients, during LT in one patient (patent ductus arteriosus), and after LT on two occasions.…”
mentioning
confidence: 99%
“…Three LTxs under single ventricle physiology have been reported to date; one was carried out after PA banding (stage I palliation), one after stage II palliation, and the other after Fontan completion . The case most similar to ours was the first one in 2006 in which a 13‐month‐old girl with single atrium, common atrioventricular valve, and intermediate type of ventricular septal defect underwent deceased donor LTx post‐PA banding.…”
Section: Discussionmentioning
confidence: 58%
“…Although many reports have described successful LTx in pediatric patients with congenital heart diseases, very few such transplantations have been performed in children with single ventricle physiology at various stages . Single ventricle physiology is a condition in which only one functional ventricular chamber pumps blood to the pulmonary and systemic circulation.…”
Section: Introductionmentioning
confidence: 99%